A comprehensive review on solar assisted cooling system. Issue 11 (18th September 2020) - Solanki, Alka; Pal, Yash; Kumar, Rajesh
Abstract : Due to increase in global warming, it is very essential to use the non-conventional source of energy in place of conventional sources of energy. Cooling is one of the most critical requirements for humankind. It also requires the traditional source. Hence there should be alternative is necessary to reduce it. Present review paper shows the comprehensive review of the solar assisted cooling system. It includes various research work done by researchers from all around the world on Solar Assisted cooling system. From the comprehensive review, it has been found that the solar assisted cooling system is essential in today's world.